2017
DOI: 10.1104/pp.17.00729
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Mechanism, Linked to Cell Density, Largely Controls Cell Division in Synechocystis

Abstract: ORCID IDs: 0000-0001-7618-4748 (M.I.); 0000-0001-8931-7722 (T.O.); 0000-0002-6113-9570 (R.S.).Many studies have investigated the various genetic and environmental factors regulating cyanobacterial growth. Here, we investigated the growth and metabolism of Synechocystis sp. PCC 6803 under different nitrogen sources, light intensities, and CO 2 concentrations. Cells grown on urea showed the highest growth rates. However, for all conditions tested, the daily growth rates in batch cultures decreased steadily over … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 97 publications
(88 reference statements)
1
8
0
Order By: Relevance
“…The intensive exploitation of this microorganism for industrial uses strongly depends on the choice of optimal growth conditions, main operational parameters including culture density ( Esteves-Ferreira et al, 2017 ; Straka & Rittmann, 2018 ), pH ( Touloupakis et al, 2016 ), temperature ( Panda et al, 2006 ), mixing rate and light environment ( Touloupakis et al, 2016 ; Singh et al, 2009 ). Even though extensive investigation showed that Synechocystis productivity is sensitive to most of the aforementioned operational parameters ( Yu et al, 2013 ; Burrows et al, 2009 ; Nanjo et al, 2010 ; Chaves, Kirst & Melis, 2015 ), it is undoubted that productivity is tightly coupled with the light absorption efficiency of optical energy conversion systems.…”
Section: Introductionmentioning
confidence: 99%
“…The intensive exploitation of this microorganism for industrial uses strongly depends on the choice of optimal growth conditions, main operational parameters including culture density ( Esteves-Ferreira et al, 2017 ; Straka & Rittmann, 2018 ), pH ( Touloupakis et al, 2016 ), temperature ( Panda et al, 2006 ), mixing rate and light environment ( Touloupakis et al, 2016 ; Singh et al, 2009 ). Even though extensive investigation showed that Synechocystis productivity is sensitive to most of the aforementioned operational parameters ( Yu et al, 2013 ; Burrows et al, 2009 ; Nanjo et al, 2010 ; Chaves, Kirst & Melis, 2015 ), it is undoubted that productivity is tightly coupled with the light absorption efficiency of optical energy conversion systems.…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, the amount of sulfate can be increased to lift the sulfur limitation of high density cultures (Figure S5, Supporting Information), which will then be limited by nitrogen instead (Table S3, Supporting Information). In a recent paper, it was proposed that Synechocystis enters stationary phase due to cell–cell interactions rather than self‐shading or other nutrient limitation. However, the final density those authors observed when cells entered stationary phase was 0.12 gDW L −1 on average, which is far below what we observe (2.88 gDW L −1 ), indicating that growth in their experiment is halted for other, unknown, reasons.…”
Section: Discussionmentioning
confidence: 99%
“…E. coli ftsZ is transcribed in an operon together with ftsA (absent in cyanobacteria) and ftsQ (i.e., the ftsQAZ operon), whereas no ftsQZ operon was observed in Anabaena , Synechocystis nor Synechococcus , where ftsZ is independently transcribed from ftsQ instead [ 109 , 147 ], contrasting the identified ftsQZ operon structure in M. aeruginosa [ 148 ]. Given that cyanobacteria are photosynthetic organisms, it is not surprising that cell division and consequently ftsZ expression patterns are dependent on the circadian clock with an expression peak near dusk in Synechococcus and Synechocystis [ 147 , 149 ]. This circadian rhythmicity in Synechococcus is governed by the essential circadian clock protein kinase KaiC, through inhibition of Z-ring formation without impacting the cellular FtsZ protein levels [ 150 ].…”
Section: The Cyanobacterial Cell Division Complex—function and Regmentioning
confidence: 99%